Visually Provoking Dissertations in Art Education - Sinner, Anita; Irwin, Rita; Jokela, Timo (Intellect, 2018)
Visually Provoking - a dynamic collection of visually oriented research about current doctoral studies from international art educators in Australia, Canada, China, Egypt, Finland, Greece, Iceland, Portugal, Spain, and the United States of America. Together we are thinking about, with and through the visual, focusing attention on practices that are reshaping our understandings of intellectual exchange in an effort to open deliberations, considerations, imaginations, and potentialities for different ways of doing research. This collection may be considered in tandem with our related book, International Perspectives on Visual Arts PhDs in Education: Provoking the Field (Intellect), which explores theoretical, methodological and practice-based accounts of doctoral studies.